2007
DOI: 10.1007/s10661-007-9710-6
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring quantity and characteristics of municipal solid waste in Dhaka City

Abstract: A reliable estimate of the quantity of solid waste generation in the city is very important for proper solid waste planning and management. However, reported estimates of solid waste generation vary widely and lead to questionability. The reported values have been derived on the assumption of demography, standard rate of waste generation by households, density values, number of trucks engaged for waste transportation and monitoring of truck movement at dump sites, etc. This diverse nature of the available data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 2 publications
0
31
0
Order By: Relevance
“…Variation occurs in waste composition dependent upon income levels [32] and category of sources. Variation also occurs based upon the extent of source reduction and recycling opportunities [36]. According to the [30] (see Table 2) the highest income group produces almost double as much household waste as the lowest income group in Dhaka.…”
Section: Waste Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation occurs in waste composition dependent upon income levels [32] and category of sources. Variation also occurs based upon the extent of source reduction and recycling opportunities [36]. According to the [30] (see Table 2) the highest income group produces almost double as much household waste as the lowest income group in Dhaka.…”
Section: Waste Generationmentioning
confidence: 99%
“…As opportunities exist to recycle wastes, the recycling facilities might have to grow at a similar pace to the generation of waste. Physical and chemical characteristics of solid waste are important to implement the waste disposal and management plan for the selection of resource and energy recovery potentials [36].…”
Section: Recyclingmentioning
confidence: 99%
“…Three primary sources of (MSW) are classified as residential area, institutional and commercial waste (Tariq et al, 2007). The two main factors that effect on type and quantity of waste are culture and society consumption pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have examined household solid waste generation and composition. [3][4][5][6][7][8][9][10][11][12][13][14] observed that in every human settlement, the microscopic unit of waste generation is the household. Due to societal changes, the household plays an important role in environmental problems associated with the generation of solid waste.…”
Section: Introductionmentioning
confidence: 99%